1997
DOI: 10.1038/sj.bmt.1700747
|View full text |Cite
|
Sign up to set email alerts
|

Serum thrombopoietin levels in patients undergoing autologous peripheral blood stem cell transplantation

Abstract: Summary:gated in patients receiving BMT and PBSCT. [5][6][7][8][9][10][11] A strong inverse correlation between serum granulocyte colony-stimulating factor (G-CSF) level and absolute neuRecently, the ligand for c-mpl has been cloned and initial studies have shown it to be the platelet regulatory trophil count has been demonstrated, 5-9 which suggests that G-CSF plays a critical role in the reconstitution of myeloid factor, thrombopoietin (TPO). To elucidate the role of TPO in the reconstitution of megakaryopoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 2 publications
1
23
0
Order By: Relevance
“…As reported, 3,4 an exponential increase in serum TPO level in response to thrombocytopenia was observed (log TPO ϭ 3.3-0.0035x; P Ͻ .001), and, as expected, 4-6 the confidence ellipse for patients with aplastic anemia (n ϭ 13) was superimposed with this regression line ( Figure 1A). Similar results were observed with the ellipse obtained with data from ALL patients at the time of diagnosis (n ϭ 42), and the regression line in these patients (log TPO ϭ 3.3-0.004x; P Ͻ .001) was not different from the regression line in controls.…”
Section: Expression and Functionality Of C-mpl In Leukemic Cells And mentioning
confidence: 67%
See 1 more Smart Citation
“…As reported, 3,4 an exponential increase in serum TPO level in response to thrombocytopenia was observed (log TPO ϭ 3.3-0.0035x; P Ͻ .001), and, as expected, 4-6 the confidence ellipse for patients with aplastic anemia (n ϭ 13) was superimposed with this regression line ( Figure 1A). Similar results were observed with the ellipse obtained with data from ALL patients at the time of diagnosis (n ϭ 42), and the regression line in these patients (log TPO ϭ 3.3-0.004x; P Ͻ .001) was not different from the regression line in controls.…”
Section: Expression and Functionality Of C-mpl In Leukemic Cells And mentioning
confidence: 67%
“…1 In humans, high TPO levels are observed in patients with thrombocytopenia of central origin secondary to myeloablative treatment or MGK deficiency, whereas low TPO levels are observed in patients with increased platelet destruction thrombocytopenia. [2][3][4][5][6][7][8] We have previously observed a significant relationship between erythropoietin (EPO) and hemoglobin levels in children with cancer, indicating that, in contrast to anemia in adult cancer patients, anemia in children with cancer is associated with decreased erythropoiesis and not with inadequate erythropoietin production. 22 To evaluate the pathophysiology of thrombocytopenia associated with leukemia at diagnosis, we evaluated serum TPO levels in patients with ALL or AML.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] However, the regulated production of TPO in therapy-induced thrombocytopenia is still being explored, especially in extrahepatic tissue such as marrow stroma. 22 Shimazaki et al 23 reported assay of serial serum TPO levels through the course of autotransplantation in nine patients, as did Ishida et al 24 for three allotransplant recipients. Similar to the results reported herein, a powerful inverse correlation between platelet counts and circulating TPO levels was recognized.…”
Section: Discussionmentioning
confidence: 87%
“…28,30 While some studies have shown an apparent correlation between TPO levels and platelet counts, standardization for interpatient variation was not considered since data points from multiple patients were pooled together in a single plot. 27,40 The importance of measuring the percentage change in TPO and its relationship to Mk mass and progenitor cell yield is illustrated in an idealized model (Figure 3). In the group II patient with a lower Mk reserve, there is a smaller percentage decrease from baseline to nadir following mobilization chemotherapy.…”
Section: Discussionmentioning
confidence: 99%